Optimalisasi Fungsi Ruang Publik Terpadu Ramah Anak di Kelurahan Untia, Kota Makassar - Muhammad Fachrul Razy; Mukti Ali; Sri Aliah Ekawati (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2020)
Public open spaces are city facilities that can be enjoyed and utilized by all ages, including children. At present, public open spaces sometimes put aside the elements of children's interests or needs in it so that children do not have a place to channel their creativity and aspirations. Kampung Nelayan Untia, Makassar City has a Child Friendly Integrated Public Space (RPTRA) provided by the government, but children prefer to play activities on the road around the house. The aim of this study is to identify the activities and conditions of children's playgrounds in the settlement area of ​​Kampung Nelayan Untia and to propose an ideal RPTRA optimization strategy. This research was conducted from December 2019 to March 2020 (3 months). The research method used is descriptive analysis, spatial, scoring, and Importance Performance Analysis (IPA). The results showed that the provision of RPTRA Untia is currently not a solution for children to carry out their activities because the availability of supporting facilities and RPTRA criteria have not been fully fulfilled which causes a lack of attractiveness for children to play or do their activities. In addition, there are several aspects that become top priorities in the development of RPTRA Untia, namely the availability of playing facilities, shade trees, and comfort.